CALCAREOUS NANNOFOSSIL BIOSTRATIGRAPHY OF UPPER CALLOVIAN-LOWER BERRIASIAN SUCCESSIONS FROM THE SOUTHERN ALPS, NORTH ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
Calcareous nannofossil biostratigraphy was investigated in uppermost Callovian-lower Berriasian sections from Southern Alps, previously detected through magnetostratigraphy, in order to achieve an integrated stratigraphic framework valid at low latitudes. Nannofossil investigations were carried out on smear slides and ultra-thin sections, revealing generally scarce to common abundances and poor-moderate preservation of nannofloras. An exhaustive taxonomic revision was performed to unambiguously separate forms which are transitional between two species and better delineate rapidly evolving groups. Four new species have been described: Zeugrhabdotus fluxus, Nannoconus puer, Nannoconus erbae, Hexalithus geometricus. Particular attention was paid to taxonomical aspects of primitive nannoconids, appearing and evolving across the early-late Tithonian transition and the Tithonian/Berriasian boundary intervals; the revision was also verified at DSDP Site 534A from Atlantic Ocean. Fourty-eight nannofossil bioevents were detected and the results help to increase potential stratigraphic resolution in this interval. Thirty-seven nannofossil bioevents in the upper Kimmeridgian-lower Berriasian interval have been directly correlated to magnetostratigraphy (CM22-CM17) revealing a systematically older stratigraphic occurrence of these taxa than previously reported. A revised and partly new Tethyan calcareous nannofossil zonation scheme is here proposed for the uppermost Callovian-lower Berriasian interval. It consists of seven bio-zones and eight subzones based on thirty-one bioevents, thirteen of them related to dissolution resistant taxa assuring highest reproducibility even in sections with high diagenetic overprint. The proposed biostratigraphic scheme gives higher resolution than previous zonations, especially for the Callovian-Kimmeridgian interval, where no biozonation was available for the Tethyan Realm.
Keywords: Calcareous nannofossils; Biostratigraphy; Magnetostratigraphy; Tethys; Late Jurassic; Southern Alps